A prospective randomised clinical trial of prophylactic antibiotic in caesarean delivery and fetomaternal outcome - Mandal, Apurba; Chattopadhyay, Shibram; Nayak, Pragnya Paramita; Panja, Sudakshina; Bhattacharyya, Shritanu; Mandal, Tanmay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infectious maternal and perinatal morbidities are 5 to 20 times more in caesarean section when compared to vaginal births. Objective of present study was to assess the rates of maternal and neonatal infectious morbidities following administration of antibiotic before skin incision compared to given after umbilical cord clamping during caesarean delivery. Methods: 185 pregnant women with gestational periods more than 34 weeks who were prepared for caesarean delivery, randomized to single dose antibiotic given either before skin incision (study group) or after umbilical cord clamping (control group). Primary outcome measures: maternal postoperative infections morbidities. Secondary outcome measures: neonatal infections morbidities with Sick Newborn Care Unit (SNCU) admissions and postoperative hospital stay of mother. Results: Surgical Site Infections (SSI) and postoperative fever were significantly less in the study group than the control group so also the lesser incidences of endometritis but no statistically significant difference in the incidence of peritonitis and wound dehiscence were observed in both groups. No significant differences were seen in neonatal infectious morbidities and SNCU admission when compared in both groups. There was significantly less mean postoperative hospital stay of mothers in the group who received prophylactic antibiotic pre-incision. Conclusions: Antibiotic given 30-60 minutes before skin incision significantly decreases maternal postoperative infectious morbidities barring neonate.